Characterization of extremely weakly ionized hydrogen plasma with a double Langmuir probe - Mozetič, Miran (Materiali in tehnologije, 2011)
Basic parameters of hydrogen plasma created in a large discharge chamber were determined using a double Langmuir probe. Plasma was created in a Pyrex cylinder with the diameter of 25 cm and the height of 80 cm by an antenna connected to a RF generator operating at the frequency of 27.12 MHz and the power of about 200 W. The antenna was a copper coil of 4 turns. The discharge chamber was pumped with an oil diffusion pump with the nominal pumping speed of 600 L/s backed by a two slage rotary pump with the pumping speed of 4.4 x 10sup{-3} msup3 ssup{-1}. The ultimate pressure of about 2 x 10sup{-3} Pa was obtained in the vacuum system after pumping for few hours. A dobule Langmuir probe was galvanic separated from the mains and placed into the centre of the discharge chamber. The probe was made from 2 tungsten rods with a diameter of 1.2 mm and separated for 2 cm. The length of un-insulated part of the rods was 17.5 mm. Plasma parameters were measured at different pressures between 0.4 and 7.2 Pa. The electron temperature reached the maximumof about kTsube = 3.5 eV at the pressure of 1 Pa. The plasma density was slowly decreasing with increasing pressure and was of the order of 10sup{15} msup{-3}, and the Debve length was rather constant at about 2 x 10sup{-4} m. The results were explaned by characteristics of an electrode less RF discharge in the E mode.
Keywords: vodikova plazma; Langmuirjeva sonda; temperatura elektronov; gostota plazme; Debyeva dolžina